Anticorrosion Behavior of Deposited Magnetite on Galvanized Steel in Saline Water Using RF-Magnetron Sputtering - Baghdad Science Journal (مجلة بغداد للعلوم, 2018)
Thin films of Magnetite have been deposited on Galvanized Steel (G-S) alloy using RF-reactive magnetron sputtering technique and protection efficiency of the corrosion of G-S. A Three-Electrodes Cell was used in saline water (3.5 % NaCl) solution at different temperatures (298, 308, 318 & 328K) using potentiostatic techniques with. Electrochemical Impedance Spectroscopy (EIS) and fitting impedance data via Frequency Response Analysis (FRA) were applied to G-S alloy with Fe3O4 and tested in 3.5 % NaCl solution at 298K.Results taken from Nyquist and Bode plots were analyzed using software provided with the instrument. The results obtained show that the rate of corrosion of G.S alloy increased with increasing the temperatures from 298 to 323K; and showed that deposition of Fe3O4 caused protection efficiency to reach 79.76% for G-S in 318K. In addition the enthalpy & entropy of activation were evaluated. Apparent energies of activation have been calculated for the corrosion process of uncoated and coated G.S alloy by sputtering technique in saline water (3.5 % NaCl). The morphological analysis was carried out using Scanning Electron Microscopy (SEM) technique.